New Effective Combined Steel Structures - Gogol, Myron; Zygun, Alina; Maksiuta, Nataliia (International Journal of Engineering and Technology, 2018)
In the article, based on the generalization of the experience of adjusting efforts in steel combined structures, it is shown, that the most rational method of regulation is calculated in the design process. This method does not require any additional material costs. It is shown that the beam on elastic intermediate supports and solid extremes is a generalized type of all possible types of beams. It was emphasized that the problem of calculating building structures, including combined, first of all should be regarded as a problem of their rational design. The results of experimental studies of combined steel truss with calculated regulation in their internal efforts are presented. Experimental studies confirmed the hypothesis about the possibility of regulating the stress deformation state (SDS) in combined structures with resilient support - system of springs and achieving an equally stressed state in the calculated cross-sections. The sufficient consistency of the experiment results with theoretical calculations is shown and the efficiency of such systems compared with the typical reaches up to 27%. The proposed nomenclature series of effective new light, with a small number of elements trussed structures. Effective combined steel structures with rational geometric parameters and calculated value adjustments of SDS were used during the construction and reconstruction of many buildings:Â Â